An Analytical Study to Improve the Efficiency of Waiting Lines in Government Institutions - Zana Najm Abdullah Nasrallah; Khalid Rahamtalla Khedir; Mohammedelameen E. Qurashi (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to analyse and improve the efficiency of waiting lines in government institutions by identifying the reasons for the length of these lines, using modern technology, overcoming obstacles, and evaluating the impact of improvements on beneficiary satisfaction and service quality. The study is based on the descriptive analytical approach, and is based on a sample of 300 employees and customers. The results showed that improving the efficiency of waiting lines enhances beneficiary satisfaction and increases the efficiency of the institution by reducing waiting times and relieving pressure on beneficiaries, while lack of resources and ineffective technology hinder the implementation of effective management strategies. Based on these results, the study recommends increasing the number of employees, improving the technical infrastructure, adopting modern technology such as electronic reservation and electronic payment systems, enhancing training and awareness for employees, in addition to establishing an effective system for monitoring and evaluating performance to improve the efficiency of waiting lines and the quality of services provided.